APPLICATION OF DATA MINING IN SELECTING SUPERIOR PRODUCTS USING THE K-MEANS AND K-MEDOIDS ALGORITHM METHODS - Munandar, Musthafa Haris (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: As a supermarket, we are committed to always improving everything, including selecting the greatest goods. To evaluate which items are more superior or popular and which are less popular, you will want a sizable amount of information sources. To select products and identify those that belong in the superior product cluster, researchers employed the clustering method. The clustering strategy uses two forms of cluster analysis, k-means and k-medoids, which have related techniques. The research results show that the k-means algorithm's Davies Bouldin value is -0.430, whereas the k-medoids algorithm's Davies Bouldin value is -1.392. This suggests that the Davies Bouldin value of the k-medoids approach is the lowest, showing that the grouping findings of the k-means method are  a better method to apply to the issue of choosing better products.            Keywords : k-means; k-medoids; clustering; algorithm; data mining  Abstract: Sebagai toko sembako, toko yuli berkomitmen untuk selalu meningkatkan segalanya, termasuk memilih barang terbaik. Untuk mengevaluasi item mana yang lebih unggul atau populer dan mana yang kurang populer, Anda memerlukan sumber informasi yang cukup banyak. Untuk memilih produk dan mengidentifikasi produk yang termasuk dalam cluster produk unggulan, peneliti menggunakan metode clustering. Strategi clustering menggunakan dua bentuk analisis cluster, k-means dan k-medoids, yang memiliki teknik terkait. Hasil penelitian menunjukkan nilai Davies Bouldin pada algoritma k-means sebesar -0,430, sedangkan nilai Davies Bouldin pada algoritma k-medoids sebesar -1,392. Hal ini menunjukkan bahwa nilai Davies Bouldin pada pendekatan k-medoids paling rendah, menunjukkan bahwa temuan pengelompokan metode k-means merupakan metode yang lebih baik untuk diterapkan pada permasalahan pemilihan produk yang lebih baik. Keywords: k-means; k-medoids; clustering; algoritma; data mining